Refratários para o transporte de alumínio líquido: fundamentos, simulação e prática industrial - Miyaji, Dan Yushin (2007)
Not only for the development of their products, the aluminum industry has engaged its efforts in services for their customers. One of them is the molten aluminum delivery (7 to 8 t) in crucibles for long distances (over 100 to 200 km). This is an advantageous practice for the customers because it allows saving energy in the melting process, and the suppliers can add value to the metal purchased. Because the process demands great amount of molten metal, a high thermal and mechanical performance of the crucible lining is needed. Thus, a systemic analysis involving design, thermodynamic, microstructure, thermal conductivity and thermo-mechanical aspects must be considered. This work aims to match these fundaments, the industrial results, the laboratory characterization of materials and the computing simulations using a software recently developed by the working team. This software is able to predict the thermal behavior of the heated containers even under operation. Therefore, based on the three pillars named theory , simulation and industrial results a new commercial refractory lining were selected improving the net volume of the crucible and saving the energy required for its pre-heating. As a second step of the resent work, one of main weak points of this refractory, the erosion resistance, was minimized